Cross-national disparities in healthcare workers’ perceptions: Examining fear of infection and confidence in the received COVID-19 vaccines amid emerging variants - Mai Hussein; Assem Gebreal; Ahmed Naeem; Asmaa Mohammed AboElela; Hoda Ali Ahmed Shiba; Jargaltulga Ulziijargal; Aesha L. E. Enairat; Ibrahim Adel; Bayan Ayash; Shehata Farag Shehata; Safar Abadi Alsaleem; Ahmed A. Mahfouz; et al. (PLoS ONE, 2025)
Variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can influence transmissibility, virulence, vaccine efficacy, the effectiveness of therapeutic agents, diagnostic accuracy, and the overall success of public health interventions. This study aimed to assess the impact of emerging variants on healthcare workers’ (HCWs) fear related to SARS-CoV-2 new variant infection and to evaluate their confidence in the received vaccines. A globally distributed cross-sectional study was performed using an online anonymous survey and face-to-face interviews between 1 st November and 5 th December 2023. The fear level was assessed by the Fear of Coronavirus Disease 19 (COVID-19) Scale (FCS), and the confidence level in the received COVID-19 vaccines was measured using the Arabic Tool for Assessment of Post-vaccination Confidence in COVID-19 vaccines (ARAB-VAX-CONF). A total of 5843 eligible HCWs completed the survey with a mean age of 32.1 ± 10.8 years. Of them, 42.5% were from the Eastern Mediterranean region, 24.2% were from the African region, 14.4% were from the Western region, and 18.9% were from other regions (Eastern Asia and Latin America). Nearly three-fourths (72.7%) were vaccinated, primarily with Pfizer (40.0%), AstraZeneca (36.8%), and Sinopharm (14.3%). Nearly two-fifths (40.5%) were in extreme fear of catching infection from the COVID-19 emerging variants. Among the HCWs who received COVID-19 vaccines, 41.0% showed good confidence in the received vaccine. Predictors of lower fear included being married [adjusted odds ratio (AOR): 0.8; 95% CI (0.7–0.9)], having a small family of two members [AOR: 0.63; 95% CI (0.5–0.78)] or three members [AOR: 0.62; 95% CI (0.51–0.72)], and being a pharmacist [AOR: 0.75; 95% CI (0.55–0.92)]. Conversely, predictors of increased fear included being divorced or widowed [AOR: 1.3; 95% CI (1.0–1.8)], residing in rural areas [AOR: 1.6; 95% CI (1.4–1.8)] or desert/mountain areas [AOR: 2.5; 95% CI (1.6–4.0)], having insufficient income and in debt [AOR: 2.5; 95% CI (2.2–3.1)], having insufficient income [AOR: 2.4; 95% CI (2.0–2.8)], and having chronic diseases [AOR: 1.2; 95% CI (1.1–1.4)]. Predictors of good confidence in the received vaccine were middle age (30–39 years) [AOR: 1.4; 95% CI (1.1–1.8)], age group 40 years and more [AOR: 1.8; 95% CI (1.4–2.3), rural/other residence [AOR: 1.3; 95% CI (1.1–1.5)], male sex [AOR: 1.3; 95% CI (1.1–1.4)], and small family members of one [AOR: 5.5; 95% CI (4.2–7.2)], two [AOR: 1.5; 95% CI (1.2–1.9)], and three [AOR: 1.3; 95% CI (1.1–1.6)]. On the other hand, having chronic diseases [AOR: 0.82; 95% CI (0.71–0.95)], having mental disorders [AOR: 0.59; 95% CI (0.51–0.69)], high family number of four [AOR: 0.78; 95% CI (0.69–0.89)], personal history of COVID-19 infection [AOR: 0.61; 95% CI (0.53–0.71)], and experiencing side effects of vaccination [AOR: 0.63; 95% CI (0.55–0.72)] were associated with low confidence regarding the received vaccine. In conclusion, HCWs exhibited notable fear of infection with SARS-CoV-2 new variants, along with low confidence in the vaccine. The study suggests realistic approaches, such as targeted interventional programs to address the fear, resolve uncertainties, and promote widespread vaccine confidence among HCWs.